1997
DOI: 10.1046/j.1365-2958.1997.4141789.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of arginine‐43 and arginine‐69 of the Hin recombinase catalytic domain in the binding of Hin to the hix DNA recombination sites

Abstract: SummaryThe Hin recombinase mediates the site-specific inversion of a segment of the Salmonella chromosome between two flanking 26 bp hix DNA recombination sites. Mutations in two amino acid residues, R43 and R69 of the catalytic domain of the Hin recombinase, were identified that can compensate for loss of binding resulting from elimination of certain major and minor groove contacts within the hix recombination sites. With one exception, the R43 and R69 mutants were also able to bind a hix sequence with an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(58 reference statements)
2
7
0
Order By: Relevance
“…The amino acid residues G38, R43 and R69 are in the N-terminal catalytic domain, and R103 and M109 are in helix E. Furthermore, the amino acid changes of R49 and R69 (see Fig. 2) have been implicated in the binding activity of Hin (Adams et al 1997). Taking these data together, it may be suggested that the unfavorable interactions between the substituted amino acids in the helix E and the neighboring amino acids in the core of the N-terminal domain in¯uence the relative positions of the two E helices at the dimer interface, which subsequently leads to the impairment of DNA binding activity.…”
Section: Conformational Change In the N-terminal Catalytic Domain Andmentioning
confidence: 98%
“…The amino acid residues G38, R43 and R69 are in the N-terminal catalytic domain, and R103 and M109 are in helix E. Furthermore, the amino acid changes of R49 and R69 (see Fig. 2) have been implicated in the binding activity of Hin (Adams et al 1997). Taking these data together, it may be suggested that the unfavorable interactions between the substituted amino acids in the helix E and the neighboring amino acids in the core of the N-terminal domain in¯uence the relative positions of the two E helices at the dimer interface, which subsequently leads to the impairment of DNA binding activity.…”
Section: Conformational Change In the N-terminal Catalytic Domain Andmentioning
confidence: 98%
“…5B, lane 3, below). Unlike other substitutions at this position (Adams et al 1997), S10G has no detrimental effect on hix binding (M. Lainé and R.C. Johnson, unpubl.)…”
Section: Properties Of Hin Mutants Used To Investigate Hin Activationmentioning
confidence: 99%
“…Media conditions, concentrations of antibiotics and lactose indicators, transductional crosses, and transformations were as reported previously (1,5,23).…”
Section: Methodsmentioning
confidence: 99%
“…Binding studies were performed as described previously, with the following modifications (1,23). Various amounts of purified Hin protein were used to determine the apparent K d values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation